Quality, Reliability, Security and Robustness in Heterogeneous Networks 9th International Conference, QShine 2013, Greader Noida, India, January 11-12, 2013, Revised Selected Papers - Singh, Karan; Awasthi, Amit K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the thoroughly refereed post-conference proceedings of the 9th International Conference on Heterogeneous Networking for Quality, Reliability, Security and Robustness, QShine 2013, which was held in National Capital Region (NCR) of India during January 2013. The 87 revised full papers were carefully selected from 169 submissions and present the recent technological developments in broadband high-speed networks, peer-to-peer networks, and wireless and mobile networks.
DSG-PC: Dynamic Social Grouping based Routing for Non-uniform Buffer Capacities in DTN with Supported Carriers -- Integrated Approach for Multicast Source Authentication and Congestion Control -- Network Selection for Remote Healthcare Systems through Mapping between Clinical and Network Parameter -- Routing Protocols in Mobile Ad-Hoc Network: A Review -- Comparative Analysis of Contention Based Medium Access Control Protocols for Wireless Sensor Networks -- Mobility based Energy Efficient Coverage Hole Maintenance for Wireless Sensor Network -- Clusterhead Selection using Multiple Attribute Decision Making (MADM) Approach in Wireless Sensor Networks.
Keywords: Computer science; Computer Communication Networks; Data protection; Data encryption (Computer science).; Computer software; Computer Science; Computer Communication Networks; Systems and Data Security; Data Encryption; Algorithm Analysis and Problem Complexity